Devising a procedure for organizing support to financial decision-making using digital technologies based on business intelligence - Leliuk, Svitlana; Stehnei, Marianna; Tkachenko, Serhii; Neimet, Viktor (Eastern-European Journal of Enterprise Technologies, 2025)
This study’s object is those business processes in the financial management system of business entities that are related to making substantiated management decisions based on aggregated financial data. The problem addressed is the lack of a comprehensive and formalized approach to the organization of decision-making support processes in the financial management system. A procedure that organizes financial decision-making has been devised by using digital technologies based on Business Intelligence (BI), which holistically combines business process modeling, the construction of reasoned conclusions, as well as the processing of structured data. The feasibility of using the BPM+ approach was clarified and a procedure for its implementation was devised. Based on the latter, the course of analytical business processes in the financial management system was modeled, based on the results of which reasoned conclusions are made and appropriate management decisions and measures could be developed. Modeling financial management tasks at the analysis stage in BPMN determines the order of implementation of business processes and the areas of responsibility for responsible persons involved in their implementation. Using an example of the process of analyzing the financial stability of the model built, the logic behind obtaining analytical conclusions using the Decision Model and Notation (DMN), which contains the Decision Requirements Diagram (DRD) and the decision table, has been formalized. Input data for forming a decision is proposed to be prepared in the environment of digital products. Given the relevance of using BI software in analytics, the example of applying MS PowerBI was applied to demonstrate the features of building and transforming an information model of financial data, which is the basis for designing interactive dashboards. The financial indicator monitoring panels constructed provide operational support for decision-making by financial managers